2006
DOI: 10.1111/j.1095-8312.2006.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of the endangered red deer from Sardinia and Mesola with further remarks on the phylogeography of Cervus elaphus corsicanus

Abstract: Red deer Cervus elaphus of the endangered populations from Sardinia and Mesola Wood, northern Italy, were analysed for genetic variation at 531 bp of the mitochondrial control region and 12 polymorphic nuclear microsatellite loci. A phylogenetic analysis was conducted including additional data from the literature to gain insight into the phylogeographical origin of the Sardinian subspecies C. e. corsicanus . Microsatellite variation was low in both populations but Sardinia showed comparatively high variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 49 publications
3
67
1
2
Order By: Relevance
“…Le teorie più accreditate, vista la completa mancanza di resti fossili, ipotizzano che la sua diffusione in Sardegna e Corsica possa essere spiegata con l'introduzione di soggetti provenienti dal Medio Oriente o dal Nordafrica avvenuta nell'ultimo periodo dell'età del bronzo (1200 -700 a. C.). Recenti indagini genetiche tuttavia propongono un'ipotesi filogeografica alternativa, supponendo un'origine italiana del Cervo sardo (Hmwe et al, 2006;, Hajji et al, 2008. Abbondante ed ampiamente diffuso su entrambe le isole fino all'inizio del XX secolo, subì in seguito una forte contrazione della distribuzione e della consistenza che portò all'estinzione della sottospecie dalla Corsica nel 1970 e alla riduzione dell'areale sardo in tre aree disgiunte e senza possibilità di interscambio di individui (Serrabus, Sulcis e Costa Verde).…”
Section: Il Cervo Sardo Distribuzione E Statusunclassified
See 1 more Smart Citation
“…Le teorie più accreditate, vista la completa mancanza di resti fossili, ipotizzano che la sua diffusione in Sardegna e Corsica possa essere spiegata con l'introduzione di soggetti provenienti dal Medio Oriente o dal Nordafrica avvenuta nell'ultimo periodo dell'età del bronzo (1200 -700 a. C.). Recenti indagini genetiche tuttavia propongono un'ipotesi filogeografica alternativa, supponendo un'origine italiana del Cervo sardo (Hmwe et al, 2006;, Hajji et al, 2008. Abbondante ed ampiamente diffuso su entrambe le isole fino all'inizio del XX secolo, subì in seguito una forte contrazione della distribuzione e della consistenza che portò all'estinzione della sottospecie dalla Corsica nel 1970 e alla riduzione dell'areale sardo in tre aree disgiunte e senza possibilità di interscambio di individui (Serrabus, Sulcis e Costa Verde).…”
Section: Il Cervo Sardo Distribuzione E Statusunclassified
“…Il Daino è oggetto di controllo numerico in diverse aree protette quali l'isola di Albarella (Parco regionale del Delta del Po), la Riserva Naturale di Berignone (Pisa), il Parco regionale di Migliarino San Rossore Massaciuccoli, il Parco Regionale della Maremma ed il Bosco della Mesola, dove la competizione da esso generata esercita ripercussioni negative sulla popolazione di Cervo, ritenuto appartenente all'ecotipo autoctono dei boschi planiziali padani (Hmwe et al, 2006). Una problematica analoga si riscontra anche nella Tenuta Presidenziale di Castelporziano ove la presenza di una numerosa popolazione di Daino risulta uno dei principali fattori limitanti per la conservazione della locale popolazione di Capriolo italico.…”
Section: La Gestione Degli Ungulati Alloctoniunclassified
“…However, compared to other populations known to be bottlenecked and/or inbred (e.g., Hasselbusch, Mesola or Corsica/Sardinia), variability values were not (2004) and Hmwe et al (2006b). For details of calculations see Hajji et al (2007) as low as might have been expected in the light of the population's demographic history (Table 1, Hmwe et al 2006a). This may be due partly to immigration of Algerian animals.…”
Section: Barbary Red Deermentioning
confidence: 91%
“…Their morphological characteristics, coupled with genetic peculiarities (Lorenzini et al 2005;Hmwe et al 2006;Zachos et al in press) make the Mesola red deer unique, deserving special protection (Lovari & Nobili 2010;Zachos & Hartl 2011;Ferretti & Mattioli 2012).…”
Section: Mature Adults Young Adults Subadults Yearlingsmentioning
confidence: 99%
“…They are the only native red deer of peninsular Italy (Castelli 1941;Mattioli 1990;Mattioli et al 2001) and show a mitochondrial DNA genotype with a sequence significantly different from those of all other populations of red deer (Lorenzini et al 2005;Hmwe et al 2006). Previous studies on morphometry of antlers, and some biometric measures, have suggested that these deer show some morphological peculiarities (small body size, reduced sexual dimorphism, persistent spotting in the summer coat, small antlers of simplified design, low reproductive performance ;Mattioli 1990Mattioli , 1993Mattioli et al 2003).…”
Section: Introductionmentioning
confidence: 99%